IMPLEMENTASI DEVELOPMENTAL STATE INDIA DALAM MENGHADAPI PATEN TRIPS DAN STRATEGI RANBAXY LAB. DALAM PERSAINGAN GLOBAL - Puguh Toko Arisanto (TRANSBORDERS: International Relations Journal, 2019)
India is hailed as one of the pharmaceutical countries for the largest generic drug in the world. India's success in the global pharmaceutical competition cannot be separated from India's efforts to adopt a developmental state scheme which Indian government has significant roles in the sustainability of domestic pharmaceutical industries through policies that benefit the domestic pharmaceutical industries. This paper will explore the implementation of Indian developmental state in dealing with TRIPs agreements and Strategies of Ranbaxy (as big domestic company that derived impacts from favorable domestic policies) in global competition through entry mode selection and location choice. Key Words : Developmental State, favorable policies, entry mode selection, location choice. India adalah salah satu negara farmasi untuk obat generik terbesar di dunia saat ini. Keberhasilan India dalam dunia farmasi tidak lepas dari upaya India dalam mengimplementasikan skema developmental state dimana pemerintah India memiliki peran besar terhadap keberlangsungan industri farmasi domestik melalui favorable policies atau kebijakan-kebijakan yang menguntungkan industri farmasi domestik. Tulisan ini akan mengeksplorasi implementasi developmental state India dalam menghadapi perjanjian TRIPs dan strategi Ranbaxy sebagai perusahaan yang mendapatkan dampak favorable policies dalam persaingan global melalui entry mode selection dan location choice. Kata Kunci : Developmental State, favorable policies, entry mode selection, location choice.